138k views
2 votes
This is the result of solving an equation to find a value(s) for the variable(s) which make the equation true.

User Boppy
by
5.2k points

2 Answers

4 votes

Answer:

Step 1: Simplify both sides of the equation.

8−2(3−x)=4x+6

8+(−2)(3)+(−2)(−x)=4x+6(Distribute)

8+−6+2x=4x+6

(2x)+(8+−6)=4x+6(Combine Like Terms)

2x+2=4x+6

2x+2=4x+6

Step 2: Subtract 4x from both sides.

2x+2−4x=4x+6−4x

−2x+2=6

Step 3: Subtract 2 from both sides.

−2x+2−2=6−2

−2x=4

Step 4: Divide both sides by -2.

−2x

−2

=

4

−2

Explanation:

User Zyndor
by
5.8k points
6 votes

Answer: it's Solution

Explanation:

User RoToRa
by
5.9k points